Research Gap Analysis of Sustainable Competitiveness in Small and Medium Enterprises (SMEs) through Community Empowerment: A Systematic Review - Kartika, Hayu; Hardjomidjojo, Hartrisari; Machfud, Machfud; Warsiki, Endang (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
The purpose of this article is to conduct a search for previous articles that will be used to find research gaps and look for internal and external factors. This research gap will be used as a basis for determining further research, namely related to sustainable competitiveness involving the community. For this purpose, an article search was conducted through the Scopus database for the last decade, namely from 2015 to 2024. The number of articles that met the required criteria was 48 articles and were used for the review results in this article. To see the relationship between the discussion of keywords in this article, the Vos Viewer tool was used. The Vos Viewer results show that there is no direct relationship between SMEs and community empowerment. In addition, the tourism sector has a role and close relationship with community empowerment compared to the industrial sector and internal and external factors were also found to have a role in sustainable competitiveness, 9 internal factors and 6 external factors were found that often appear. This article also provides recommendations related to research that may be carried out in the future.